A MONOGRAPH ON SPACE: KAHN ARCHITECTURE AND TURRELL INSTALLATION - Seda Yazıcı; Merve Türkköylü; Erkan Aydıntan; Selen Rumeysa Ünlü (Livenarch+ Journal)
The way design disciplines and art look at space in terms of their reasonings and their perceptions shows similarities and differences between past and present. This is also true for architecture, that creates space, and installation art, that presents spatial narratives. In the readings, no study was found in which the concept of space was monographically handled in the context of its relationship with architecture and installation art and examined in depth with case analysis. From this point of view, the hypothesis that the multidimensionality of space can be read through the architecture of Louis Kahn and the installation of James Turrell was put forward and a monographic examination was carried out.The study consists of determining the sample, research and analysis. The selection of the names in question was influenced by the fact that their ways of dealing with space can be read both through their own discourses and publications on their works, as well as the fact that they are award winners. Theses, scientific research papers, artistic criticism texts, book/book chapters, interviews and biography documentaries were used as research material. In the examinations made by content analysis, firstly, the concepts expressing the architect and artist's view of space were determined. Then, common and different concepts in both fields were ranked according to their frequency of use. Thus, representing Louis Kahn and James Turrell's approaches to space with the concepts frequently encountered in the literature and illustrating them has been adopted as the method of the study.